Coplanar waveguide-fed ultra-wideband antenna with WLAN band - Chaiyong Soemphol; Niwat Angkawisittpan (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A coplanar waveguidefed ultra-wideband antenna with extended transmission band to WLAN frequency is investigated. The proposed antenna consists of a modified semi-circular patch and staircase of ground plane. The prototype is fabricated on a low cost FR4 substrate with dielectric constant of 4.4 with thicknes of 0.8 mm. The overall dimensions of proposed UWB antenna are 34 mm x 40 mm. The simulation and experimental results have been shown that the proposed antenna archives low VSWR over transmission bandwidth from 2.10 - 12.7 GHz to cover both WLAN and UWB bands.  The average gain is 3.87 dBi. It depicts nearly omni-directional radiation pattern like dipole antenna. Moreover, the fabricated prototype antenna shows a good agreement between the simulated and measured results